Circulating tumour cell increase as a biomarker of disease progression in metastatic castration-resistant prostate cancer patients with low baseline CTC counts. (7th May 2018) - Lorente, D; Olmos, D; Mateo, J; Dolling, D; Bianchini, D; Seed, G; Flohr, P; Crespo, M; Figueiredo, I; Miranda, S; Scher, H I; Terstappen, L W M M; et al.
Abstract: Background: The development of treatment response and surrogate biomarkers for advanced prostate cancer care is an unmet clinical need. Patients with baseline circulating tumour cell (BLCTCs) counts <5/7.5 mL represent a good prognosis subgroup but are non-evaluable for response assessment (decrease in CTCs). The aim of the study is to determine the value of any increase in CTCs (CTC progression) as an indicator of progression in prostate cancer patients with low pre-treatment CTCs (<5). Patients and methods: We carried out a post hoc analysis of patients with BLCTCs < 5 treated in the COU-AA-301 (abiraterone or placebo + prednisone) and IMMC-38 (chemotherapy) trials. The association of CTC progression (increase in CTCs at 4, 8 or 12 weeks) with overall survival (OS) was evaluated in multi-variable Cox regression models. Performance of survival models with and without CTC progression was evaluated by calculating ROC curve area under the curves (AUCs) and weighted c-indices. Results: Overall, 511 patients with CTCs < 5 (421 in COU-AA-301 and 90 in IMMC-38) were selected; 212 (41.7%) had CTC progression at 4, 8 or 12 weeks after treatment initiation. CTC progression was associated with significantly worse OS [27.1 versus 15.1 m; hazard ratio (HR) 3.4 (95% confidence interval [CI] 2.5–4.5; P < 0.001)], independent of baseline CTCs and established clinical variables. Adding CTC progression to the OS model significantly improved ROC AUC (0.77 versus 0.66; P < 0.001). Models including CTC progression had superior ROC AUC (0.77 versus 0.69; P < 0.001) and weighted c-index [0.750 versus 0.705; delta c-index: 0.045 (95% CI 0.019–0.071)] values than those including CTC conversion (increase to CTCs ≥ 5). In COU-AA-301, the impact of CTC progression was independent of treatment arm. Conclusions: Increasing CTCs during the first 12 weeks of treatment are independently associated with worse OS from advanced prostate cancer in patients with baseline CTCs < 5 treated with abiraterone or chemotherapy and improve models with established prognostic variables. These findings must be prospectively validated.